Arch Pharm Pharm Sci 2017
DOI: 10.29328/journal.hps.1001004
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Medicines: Formulation Considerations

Abstract: The use of unlicensed and off-label medicines in children is widespread and has raised an increasing concern over the last years. The majority of medicines taken by children are extemporaneously compounded by pharmacist, and there is a lack of information regarding bioavailability, suitability and stability. These formulations must be prepared from pure active substance and not from commercially available dosage forms. The development of paediatric formulations, particularly those suitable for very young child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Extemporaneous preparations are not required to meet certain standards from the regulator [ 92 ]. The main purpose of regulation is to ensure the efficacy and safety of drug use [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extemporaneous preparations are not required to meet certain standards from the regulator [ 92 ]. The main purpose of regulation is to ensure the efficacy and safety of drug use [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounding is an important activity of pharmacists that aims to provide dosage forms or certain doses of unavailable medicine among licensed drugs [ 2 ]. Extemporaneous preparations remain widely used, especially for pediatric patients [ 3 , 4 ], patients with rare diseases [ 5 , 6 ], patients who require special dosage forms [ 7 ] or certain doses/strengths, and dermatological patients [ 8 , 9 ]. Compounding is performed by various pharmaceutical services, including in pharmacies, hospitals, and health centers [ 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of pharmacies provide compounding services but the prevalence of extemporaneous dispensing is generally low, estimated to be less than 5% of health products (Wiedyaningsih et al, 2017). Generally, prevalence is higher for dermatological and pediatric products due to unavailability of commercial preparations that are tailored towards a specific patient condition (Moulis et al, 2018;Fátima, 2017;Pappas et al, 2002). A comprehensive literature searches for the period (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) revealed that the occurrence of extemporaneously compounded products in most pharmacies in United Kingdom, New Zealand, Belgium, France, Australia and the Netherlands to be less than 5% (Kristina et al, 2017).…”
Section: Prevalence Of Extemporaneous Compoundingmentioning
confidence: 99%